+0  
 
0
240
1
avatar

(3x-2)!+=1

Guest Aug 15, 2017
 #1
avatar+2190 
+1

Let's think about this problem. There are 2 solutions to \(y!=1\). It is 0 and 1. Therefore, we need to set \(3x-2\) equal to both 0 and 1:

 

\(3x-2=0\) Add 2 to both sides.
\(3x=2\) Divide by 3 on both sides.
\(x=\frac{2}{3}\)  
   

 

Let's do the other one now!

 

\(3x-2=1\) Add 2 to both sides.
\(3x=3\) Divide by 3 on both sides.
\(x=1\)  
   

 

Therefore, x=1 and 2/3

TheXSquaredFactor  Aug 15, 2017

53 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.